Relationship between reduced forced expiratory volume in one second and the risk of lung cancer: a systematic review and meta-analysis - Wasswa-Kintu, S; Gan, W Q; Man, S F P; Pare, P D; Sin, D D (Thorax, 2005)
Background: Individuals with severely impaired lung function have an increased risk of lung cancer. Whether milder reductions in forced expiratory volume in 1 second (FEV1) also increase the risk of lung cancer is controversial. Moreover, there is little consensus on whether men and women have similar risks for lung cancer for similar decreases in FEV1. Methods: A search was conducted of PubMed and EMBASE from January 1966 to January 2005 and studies that examined the relationship between FEV1 and lung cancer were identified. The search was limited to studies that were population based, employed a prospective design, were large in size (⩾5000 participants), and adjusted for cigarette smoking status. Results: Twenty eight abstracts were identified, six of which did not report FEV1 and eight did not adjust for smoking. Included in this report are four studies that reported FEV1 in quintiles. The risk of lung cancer increased with decreasing FEV1. Compared with the highest quintile of FEV1 (>100% of predicted), the lowest quintile of FEV1 (<∼70% of predicted) was associated with a 2.23 fold (95% confidence interval (CI) 1.73 to 2.86) increase in the risk for lung cancer in men and a 3.97 fold increase in women (95% CI 1.93 to 8.25). Even relatively small decrements in FEV1 (∼90% of predicted) increased the risk for lung cancer by 30% in men (95% CI 1.05 to 1.62) and 2.64 fold in women (95% CI 1.30 to 5.31). Conclusion: Reduced FEV1 is strongly associated with lung cancer. Even a relatively modest reduction in FEV1 is a significant predictor of lung cancer, especially among women.